2018
DOI: 10.1029/2018jg004613
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Soil Respiration in a Subalpine Landscape Using Point, Terrain, Climate, and Greenness Data

Abstract: Landscape carbon (C) flux estimates help assess the ability of terrestrial ecosystems to buffer further increases in anthropogenic carbon dioxide (CO 2 ) emissions. Advances in remote sensing have led to coarse-scale estimates of gross primary productivity (GPP; e.g., MODIS 17), yet efforts to develop spatial respiration products are lacking. Here we demonstrate a method to predict growing season soil respiration at a regional scale in a mixed subalpine ecosystem. We related field measurements (n = 396) of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 91 publications
2
11
1
Order By: Relevance
“…The 2 between 8-day aggregated HPMbased ET estimation and data retrieved from Mu et al (2013) achieves 0.65 (Figure S1). Berryman et al (2018) developed a random forest model to predict growing season soil respiration at subalpine forests in the Southern Rocky Watershed for validation, our results are comparable to other studies that focus on sites within the same ecoregion (e.g., Berryman et al, 2018). shows the absolute value of monthly mean difference in ET (Fig.…”
Section: Use Case 2: Ecoregion-based Data-driven Hpm Model For Et and Estimationsupporting
confidence: 81%
See 2 more Smart Citations
“…The 2 between 8-day aggregated HPMbased ET estimation and data retrieved from Mu et al (2013) achieves 0.65 (Figure S1). Berryman et al (2018) developed a random forest model to predict growing season soil respiration at subalpine forests in the Southern Rocky Watershed for validation, our results are comparable to other studies that focus on sites within the same ecoregion (e.g., Berryman et al, 2018). shows the absolute value of monthly mean difference in ET (Fig.…”
Section: Use Case 2: Ecoregion-based Data-driven Hpm Model For Et and Estimationsupporting
confidence: 81%
“…Our (Berryman et al, 2018;Mu et al, 2013). Annual differences between evergreen forests and deciduous forests are around 50 −2 , which is comparable to Berryman et al 2018). Similar dynamics were also observed at regions that are have different climate conditions.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A good agreement (R 2 : 0.80-0.97; RMSE: 279-978 g CO2 m −2 yr −1 ) between simulated and observed ecosystem respiration (RECO) was observed (Figure 8). Although the simulative accuracy was good compared to previous studies, for example, studies on soil respiration simulation at global and ecosystem scales which showed RMSE values of 696-2010 g CO2 m −2 yr −1 [3,28,62,63]. It is worth note that the present RMSE values were still quite high (12-43% of the observed respiration), which calls for more efforts on ecosystem/soil respiration modeling.…”
Section: Uncertaintiescontrasting
confidence: 51%
“…Several studies have recently been conducted to model the spatial distribution of soil respiration (R s ) at alpine grasslands [25] and forests [26,27] using the satellite-based products including land surface temperature (LST) and spectral vegetation index (NDVI or EVI) or leaf area index (LAI). By incorporating the terrain information, Berryman et al [28] estimated R s in a typical of the Southern Rocky Mountains with a coefficient of determination (R 2 ) of 0.45. Jägermeyr et al [29] firstly developed the models of global R e according to forested and non-forested biomes.…”
mentioning
confidence: 99%